New approach to generate meat color in meat processing - Chau , Thanh Tuan (Journal of Technical Education Science, 2017)
Color is one of the most important factors of sensory quality of meat products to attract consumers. In meat and meat products, myoglobin compounds in a natural form or ligand with other additives mainly contribute the pigments. Nitrosomyoglobin is the main pigment of cooked ham, while Zn-protoporphyrin (ZnPP) is that of dry-cured ham. The nitrite related myoglobin is not referred because of the cancer risks of created nitrosamines. The latter is safe but it needs a long period to develop in the dry-cured ham and is believed that related to heme and the metal core of the heme. Therefore, variant studies was carried out to find factors that can enhance the formation of ZnPP in not only the hams but also others products.